2017
DOI: 10.1080/07315724.2017.1331385
|View full text |Cite
|
Sign up to set email alerts
|

Whole Red Grape Juice Reduces Blood Pressure at Rest and Increases Post-exercise Hypotension

Abstract: We conclude that juice promotes a reduction in BP at rest and is also capable of improving PEH in individuals with hypertension, but these effects are dependent on the initial BP values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…One way to easily change food intake might be accomplished by using food supplements, which have a synergistic effect with the application of ST. Some food supplements have been shown to decrease arterial pressure when used with aerobic training [56,57,58,59] or alone. On the other hand, some food supplements might have a positive effect alone but when used simultaneously with exercise might cause side effects, such as post-exercise hypotension [60,61,62,63,64,65,66].…”
Section: Introductionmentioning
confidence: 99%
“…One way to easily change food intake might be accomplished by using food supplements, which have a synergistic effect with the application of ST. Some food supplements have been shown to decrease arterial pressure when used with aerobic training [56,57,58,59] or alone. On the other hand, some food supplements might have a positive effect alone but when used simultaneously with exercise might cause side effects, such as post-exercise hypotension [60,61,62,63,64,65,66].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, finding concluded that juice promotes a reduction in BP at rest and is also capable of improving PEH in individuals with hypertension. 43…”
Section: Effect On Hypertensionmentioning
confidence: 99%
“…Therefore, apples and grapes are useful supplements in the promotion of a decrease in oxidative stress and inflammation. Few research have been performed analyzing the effect of apple and grape intake and together suggest that both promote effect of recovery blood pressure or time to exhaustion (DELEY et al, 2017;NETO et al, 2017), outcomes linked to health rather than performance. During the two testing sessions, healthy subjects completed an endurance test at a high percentage of their maximal aerobic power and time to exhaustion was measured.…”
Section: Grapes and Applementioning
confidence: 99%